Country Market survey : Nigeria - International Economic surveys (International economic survey na, 1977)
Nigeria civil aviation activity is on the threshold of even more dynamic expansion. So far, domestic aviation has been virtually limited to daytime flight, but the Nigerian civil aviation is committed to making Nigeria one of the few countries with precision navigation aids.
nmn, 17/04/19
Ref
Keywords: Economic survey - Nigeria; Market survey - Nigeria; Nigeria